Development of psychiatric risk evaluation checklist and routine for nurses in a general hospital: ethnographic qualitative study - Camargo, Ana Luiza Lourenço Simões; Maluf Neto, Alfredo; Colman, Fátima Tahira; Citero, Vanessa de Albuquerque (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: There is high prevalence of mental and behavioral disorders in general hos-pitals, thus triggering psychiatric risk situations. This study aimed to develop a psychiatric risk assessment checklist and routine for nurses, the Psychiatric Risk Evaluation Check-List (PRE-CL), as an alternative model for early identification and management of these situations in general hospitals. DESIGN AND SETTING: Ethnographic qualitative study in a tertiary-level private hospital. METHOD: Three hundred general-unit nurses participated in the study. Reports were gathered through open groups conducted by a trained nurse, at shift changes for two months. The questions used were: “Would you consider it helpful to discuss daily practice situations with a psychiatrist? Which situations?” The data were qualitatively analyzed through an ethnographic approach. RESULTS: The nurses considered it useful to discuss daily practice situations relating to mental and be-havioral disorders with a psychiatrist. Their reports were used to develop PRE-CL, within the patient overall risk assessment routine for all inpatients within 24 hours after admission and every 48 hours thereafter. Whenever one item was present, the psychosomatic medicine team was notified. They went to the unit, gathered data from the nurses, patient files and, if necessary, attending doctors, and decided on the risk management: guidance, safety measures or mental health consultation. CONCLUSION: It is possible to develop a model for detecting and intervening in psychiatric and behav-ioral disorders at general hospitals based on nursing team observations, through a checklist that takes these observations into account and a routine inserted into daily practice.